Structural heterogeneity and partial budgetary cooperation in a monetary union - Séverine Menguy (Kiel Institute for the World Economy (IfW), 2012)
The paper analyzes the usefulness of budgetary cooperation in a monetary union, even if it is limited to a subgroup of countries with close structural characteristics. The author finds that its advantages depend on the nature of the shocks and on the width of the heterogeneities within the monetary union. Budgetary cooperation between countries where the sensitivities of economic activity to public expenditures and to foreign economic activity are sufficiently high, is beneficial to stabilize symmetric demand shocks. It is beneficial to stabilize symmetric supply shocks if it concerns a sufficiently large number of countries. On the contrary, budgetary cooperation is generally detrimental to stabilize asymmetric demand or supply shocks.
Keywords: E61; E63; F41; F42; 330; economic stabilization; monetary union; budgetary cooperation; demand shocks; supply shocks; structural heterogeneity